COMPETENCY TRAINING: MEASURING THE DETERMINANTS OF INTENTION - Nurhidayati Nurhidayati; Aprih Santoso; Suryanto Suryanto (Universitas Padjadjaran, 2021)
The research aims to empirically analyze the effects of motivation, perceived costs, perceived convenience and perceived usefulness on student interest in participating in competency training. The research object is students of the Management Study Program, Faculty of Economics, Semarang University. The number of samples was 96 students. The sampling technique used a systematic random method, namely students of the Management Study Program, Faculty of Economics. Technique data analysis used multiple regression and classical assumption tests as well as hypothesis testing (t test and F test). The results showed that: (1) Motivation has a positive and significant effect on interest in participating in competency training. (2) Training costs have a negative effect on interest in participating in competency training. (3) Perception of convenience has a positive effect on interest in participating in competency training. (4) Perceived benefits have a positive effect on interest in participating in competency training. The conclusion is that motivation, perceived convenience and benefits have a positive and significant effect on the intention to attend competency training, while the training costs have negative results. The implication: (1) The quality of the training needs to be improved, namely by using a lot of case study questions and practice questions. (2) The material is kept as simple as possible so that it is easily understood by the trainees. (3) Cooperating with institutions that issue competency training tests.